Pengaruh Model Pembelajaran ( Somatic, Auditory, Visual, Intelectual) Savi Dan Discovery Learning Ditinjau Dari Motivasi Berprestasi Siswa Terhadap Prestasi Belajar Fisika Materi Gerak Harmonik Sederhana - Badrul Wajdi; Baiq Heni Jumiati (Universitas Hamzanwadi, 2018)
This study aims to determine: 1) The effect of SAVI learning model and Discovery Learning on Physics learning achievement. 2) The influence of student achievement motivation high and low on the achievement of learning physics. 3) The existence of interaction between SAVI learning model and Discovery Learning with achievement motivation learn to Physics learning achievement. This type of research is quasi experimental research. The population in this study were all students of grade X MA Mu'allimin NW Pancor. The sample was determined by cluster random sampling technique. Data collection techniques used questionnaires and multiple choice tests. hypothesis in this research use two way anava test. Based on the results of data analysis can be concluded that the first hypothesis there is influence with indigo Fhitung 6,00 > Ftabel is 4.04. From the results of the analysis, the first hypothesis concludes that, the SAVI model learning resulted in better learning achievement than learning using the Discovery Learning model. in the second hypothesis it produces Fhitung 65,45 > Ftabel is 4.04. From the results of the analysis, then the second hypothesis concluded the achievement of students who have high achievement motivation is better than the achievement of students who have low achievement motivation. While in the third hypothesis has no interaction with the value Fhitung -3,53 Ftabel is 0.04